Surrendered love - Hilton, Laura V., 1963- (The Amish of Webster County, 2013)
"Acting on a long-kindled attraction, Janna Kauffman and Hiram 'Troy' Troyer find themselves catapulted into a love that will test their faith and question their values"--Provided by publisher.